Privacy-Enhancing Technologies in Biomedical Data Science - Cho, Hyunghoon; Froelicher, David; Dokmai, Natnatee; Nandi, Anupama; Sadhuka, Shuvom; Hong, Matthew M; Berger, Bonnie (Annual review of biomedical data science, 2024)
The rapidly growing scale and variety of biomedical data repositories raise important privacy concerns. Conventional frameworks for collecting and sharing human subject data offer limited privacy protection, often necessitating the creation of data silos. Privacy-enhancing technologies (PETs) promise to safeguard these data and broaden their usage by providing means to share and analyze sensitive data while protecting privacy. Here, we review prominent PETs and illustrate their role in advancing biomedicine. We describe key use cases of PETs and their latest technical advances and highlight recent applications of PETs in a range of biomedical domains. We conclude by discussing outstanding challenges and social considerations that need to be addressed to facilitate a broader adoption of PETs in biomedical data science.